The treatment of the thumb carpometacarpal arthritis by an open synovectomy with a joint debridement: evaluation of long-term postoperative treatment results - Tamulevičius, Martynas; Minderis, Mindaugas; Pajėda, Andrius (Lietuvos chirurgija, 2018)
[full article and abstract in Lithuanian; abstract in English]Background. Several systemic reviews have showed that no surgical technique for treating thumb carpometacarpal osteoarthritis (TMC osteoarthritis) is superior by results. Our goal was to investigate long-term treatment results of open synovectomy with joint debridement and compare them with other widely popular surgical techniques.Methods. In this retrospective cohort study we evaluated 19 patients (20 thumbs) with II–IV stage TMC osteoarthritis. All patients were treated by a single surgeon with open synovectomy with joint debridement. Procedure covered synovectomy and removal of free bodies and osteophytes. We divided patients by follow-up into two groups: up to 4.5 years (N = 10), more than 4.5 years (N = 9). We evaluated pain in numeric pain rating scale, postoperative hand function (tip and lateral pinch, opposition range, QuickDASH questionnaire score), postoperative articular status (two views hand x-rays) and time of full recovery. All results were compared with other popular surgical techniques.Results. Our treatment significantly reduced pain for all patients, same as compared techniques. A complete relief of pain in longer follow-up group did not differ from compared techniques. There were not significant differences in QuickDASH scores. Also our patients had the same or higher tip and lateral pinch strength. In compared studies was seen the main complication – proximalisation of first metacarpal. Our patients did not have that. Time of full recovery was in average 3 months, which is significantly less that in techniques with K-wire fixation.Conclusions. Our surgical technique’s long-term treatment results do not differ from widely popular techniques in pain reduction and hand function. Our patients hand more advantageous postoperative joint status, which had caused faster recovery. That is why open synovectomy with joint debridement would become a primary choice for treating TMC osteoarthritis.
Keywords: thumb carpometacarpal joint, osteoarthritis, open synovectomy, debridement